The conjugation operator on Aq(G) - Sanjiv Kumar Gupta (International Journal of Mathematics and Mathematical Sciences)
Let q>2. We prove that the conjugation operator H does not extend to a bounded operator on the space of integrable functions defined on any compact abelian group with the Fourier transform in lq.